(untitled) (Journal of Social Sciences Review, 2023)
This paper investigates the effect of students’ cognitive and emotional engagement on learning achievement in government primary male schools. Academic achievement was assessed through academic success and academic productivity. Data were gathered and utilized a survey questionnaire with 120 male primary school teachers as the sample. Descriptive Statistics and Pearson correlation were used to assess the data that had been obtained. Analysis of the data revealed a strong positive correlation between student cognitive engagement with and academic success and academic productivity. Based on the findings, the study concluded that educational stakeholders should concentrate on student engagement as a key factor that influences a distal outcome, such as increased academic production and accomplishment. The study recommended that educators, decision-makers, and the research community pay closer attention to and identify ways to improve student involvement. Additionally, educators should create and implement a variety of classroom activities that appeal to students’ cognitive functions. The implications of the findings for academic programs, institutions, teachers, and students are far larger. They support primary educational institutions by providing important data for student involvement and academic success. Additionally, the findings open up fresh avenues and perspectives for further study.